Quantitative Analysis for Business Decisions. - Wheeler, John T.; Griffin, Charles H. (The Accounting Review, 1966)
The article reviews the book "Quantitative Analysis for Business Decisions," by Harold Bierman Jr., Charles P. Bonini, Lawrence E. Fouraker and Robert K. Jaedicke.